The social characteristics and scientific-methodological foundations of the concept of corruption - Sayfiddinovich, Aripov Alisher (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the social characteristics of corruption and explore the philosophical foundations for its prevention. By emphasizing the moral and social dimensions, the research seeks to understand how corruption disrupts social structures, weakens trust, and undermines justice, while identifying philosophical strategies that can guide preventive measures. Research Methodology: The study employs a qualitative philosophical approach, using descriptive and analytical methods to examine corruption as a moral and social phenomenon. It integrates conceptual analysis, normative reasoning, and interpretive evaluation of ethical and social theories related to corruption and public morality. Results: Findings reveal that corruption is not only a legal or economic issue but also a deeply rooted social pathology arising from distorted values and weak moral consciousness. The philosophical analysis identifies ethical education, social responsibility, and civic virtue as essential instruments in combating corruption’s normalization in society. Conclusions: The research concludes that effective anti-corruption efforts must be grounded in moral reconstruction and collective ethical awareness. Philosophical inquiry provides a critical framework for redefining public virtue and re-establishing integrity as a social norm. Limitations: This study is theoretical and lacks empirical validation, requiring further sociological and policy-based research to operationalize its philosophical insights. Contribution: The paper contributes to the interdisciplinary discourse on corruption by linking social philosophy with practical governance strategies for moral and institutional reform.